The Influence of Fleet Management on Operational Performance through Operational Efficiency in Indonesian Transportation Companies - Fajar Akbar Islamic; Bayu Riyadi Widhiyanto; Grace Vita Vidyani; Betty Nila Purnamasari; Setyasnomo Setyasnomo (Sanskara Manajemen Dan Bisnis, 2026)
This study examines the effect of Fleet Management on Operational Performance through Operational Efficiency in Indonesian transportation companies. A quantitative explanatory research design was employed using primary data collected from 100 respondents directly involved in fleet and transportation operations, including operational managers, fleet supervisors, dispatch officers, maintenance personnel, and drivers. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS version 3. The results show that Fleet Management has a positive and significant effect on Operational Efficiency. Fleet Management also has a positive and significant direct effect on Operational Performance, with a coefficient of 0.291, a t-value of 3.241, and a p-value of 0.001. Furthermore, Operational Efficiency significantly affects Operational Performance. The indirect effect of Fleet Management on Operational Performance through Operational Efficiency is also significant. The Variance Accounted For value of 56.89% indicates partial mediation. These findings demonstrate that effective fleet management practices, including preventive maintenance, route optimization, fuel monitoring, vehicle utilization, and real-time fleet supervision, improve operational performance both directly and through enhanced operational efficiency. The study highlights the importance of integrated and technology-based fleet management systems in supporting cost control, service reliability, productivity, and sustainable competitiveness in Indonesian transportation companies.